O Programa Bolsa Família: seus impactos na construção da cidadania - Nacif, Luzimar Calazans (2009)
This school work discusses the political social and economic impacts caused by the Bolsa Familia Program in the construction of citizenship. The program, understood as an expression of the National Policy for Social Assistance in the present situation of the Brazilian state, also demonstrates the involvement of electoral political patronage, the discussion on the universalization of social rights and their implications with the Bolsa Familia and the relationship to citizenship. Social movements and the new possibilities of control of social policies through participatory citizenship. To reach the goals we used information from the PNAD , through qualitative research based on the systematization of secondary data provided by accredited institutes